Four new species of Scaphisoma Leach with maculate elytra (Coleoptera: Staphylinidae: Scaphidiinae) from Mexico, with new records and comments on S. balteatum Matthews - Fierros-López, Hugo Eduardo (Zootaxa, 2006)
Four new species of Scaphisoma are described from Jalisco, Morelos and Oaxaca, Mexico: Scaphisoma jaliscanum sp. nov., S. cortesaguilari sp. nov., S. opochtli sp. nov. and S. versicolor sp. nov. New distributional records and comments on S. balteatum are included: it is recorded for the first time from Costa Rica and Jalisco. A key to Mexican species of Scaphisoma with maculate elytra and data on their fungal hosts are provided.